PENGARUH PROFITABILITAS, STRUKTUR ASET DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Saswanto, Saswanto; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the influence of profitability, assets structure, and firm size to the capitalstructure. The population of this research is 12 automotive companies which are listed in Indonesia StockExchange. The sample collection technique has been conducted by using purposive sampling therefore, 8companies have been selected as samples. The analysis technique has been done by using multiple linearregressions analysis. The result of the test shows that profitability, assets structure, and firm size are fit / feasibleto be used as the predictor of capital structure. This result indicates that profitability, assets structure, and firmsize is feasible as the explanatory variables of capital structure. The result of the test shows that profitability hasnegative and significant influence to the capital structure, and assets structure has positive and significantinfluence to the capital structure whereas firm size does not have any influence to the capital structure.Keywords: profitability, assets structure, firm size and capital structure.